The role of Internet technology in future mobile data systems. - Guardini, I.
Mobile telephony and the Internet are the fastest growing businesses in the telecommunications market. This is why most operators and service providers are looking after the development of new services in both sectors, and newcomers are expected to enter the arena. The mobile operators foresee an increasing share of their revenues coming from new data services, while Internet service providers are attracted to wireless technology and mobility services both to reduce costs within the last-mile segment and to enrich their market share, providing ubiquitous access to the Internet and corporate intranets. In this scenario several wireless overlay networks will coexist, and their interworking will be a challenging objective. The employment of Internet technology, with its novel mobility and security extensions, seems to be the most attractive option for achieving that goal. In addition, the migration to a full IP network architecture, even within each specific wireless domain, will be another promising opportunity, already under consideration within several technical and standardization bodies. The envisioned role of Internet technology makes it worthwhile to undertake significant research efforts on the development of innovative IP-based mobile data systems, and opens promising opportunities for both telcos and Internet service providers.
Keywords: IP network architecture; Internet service providers; Internet technology; Business; Corporate intranets; Data services; Mobile computing; Mobile data systems; Mobile operators; Mobile telephony; Mobility services; Network operators; Revenues; Standardization bodies; Telecommunications market; Wireless technology